PENGARUH KECERDASAN, TIPE KEPRIBADIAN, PEER FEEDBACK DAN SUPERVISI KLINIS TERHADAP KINERJA GURU - Deza Zalia Permata Dewi; Zulkifli Zulkifli; Nasruji Nasruji (Pascasarjana Universitas Riau Kepulauan, 2022)
The purpose of this research was to analyze the effect of intelligence, personality type, peer feedback and clinical supervision conducted by the principal on teacher performance partially and simultaneously. This research is a quantitative research using a descriptive design. The population of this study were all civil servant teachers at SMKN 1 and SMKN 3 Batam in the 2021/2022 academic year. The sample interpretation of this study by saturated of 104 PNS teachers. The data from this study were obtained by using a questionnaire, and had been tested for validity and reliability. Data analysis used double linear regression by SPSS 26. The results of the study concluded that intelligence had a partially significant effect toward teacher performance. personality type had a partially significant effect toward teacher performance, peer feedback had a partially significant effect toward teacher performance, and clinical supervision had a partially significant effect on teacher performance, and intelligence, personality type, peer feedback and clinical supervision together affect teacher performance..